2014
DOI: 10.1063/1.4868478
|View full text |Cite
|
Sign up to set email alerts
|

Invariants of the electromagnetic field

Abstract: We present a constructive proof that, in electrodynamics, all of the gauge-invariant Lorentz scalars and pseudoscalars can be expressed as functions of the quadratic ones.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…As we will use the fields D and H to describe the dynamics of the theory, we need their time development. The time development of the D field is directly determined by Ampère's law (21). In order to extract the time development of H from Faraday's law (23), it is necessary to use the constitutive relations (18).…”
Section: First-order Formulation Of Nonlinear Electrodynamicsmentioning
confidence: 99%
“…As we will use the fields D and H to describe the dynamics of the theory, we need their time development. The time development of the D field is directly determined by Ampère's law (21). In order to extract the time development of H from Faraday's law (23), it is necessary to use the constitutive relations (18).…”
Section: First-order Formulation Of Nonlinear Electrodynamicsmentioning
confidence: 99%
“…Studies on nonlinear electrodynamics (NLED) have a long history in physics and dates back from 1934 when Born and Infeld [1] proposed a nonlinear modification of Maxwell theory with the aim to correct the infinities of the selfenergy and the fields of a point charge. Such model is constructed from the only Lorentz electromagnetic invariants F = F µν F µν and G = F µν F µν [2] and it has been shown that it can be derived as an effective action from quantized string theory [3]. As a second well known nonlinear electrodynamics example we found the Heisenberg and Euler model [4], which is capable of explaining scattering processes between photons and creation of electron-positron pairs.…”
Section: Introductionmentioning
confidence: 93%
“…The argument is straightforward. Any gauge and Poincaré invariant quantity built out of the electromagnetic vector potential A µ and its field strength F µν alone may be constructed out of only [6] the following two well-known gauge invariant and Lorentz scalar or pseudo-scalar quantities,…”
Section: Introductionmentioning
confidence: 99%